Intersphincteric Resection for Low Rectal Tumors - Schiessel, Rudolf; Metzger, Peter (Springer Vienna : Imprint: Springer, 2012)
The work describes a new method of sphincter salvage in surgery of rectal cancer. Low tumors of the rectum are traditionally treated with amputation of the rectum. However, this operation is not well-received by patients, since it results in a permanent colostomy. By contrast, intersphincteric resection allows sphincter salvage even in low tumors and is now widely accepted among experts in the field of colorectal surgery. The book will describe the basics (pathology,physiology, radiology) as well as the surgical technique and its different modifications.